2011
DOI: 10.1371/journal.pone.0025006
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid Metabolites in Serum: Intraindividual Variation and Associations with Coronary Heart Disease, Metabolic Syndrome and Diabetes Mellitus

Abstract: Bile acids (BAs) regulate glucose and lipid metabolism. In longitudinal and case-control-studies, we investigated the diurnal variation of serum concentrations of the 15 major BAs as well as the biosynthetic precursor 7α-hydroxy-4-cholesten-3-one (C4) and their associations, respectively, with coronary artery disease (CAD), diabetes mellitus type 2 (T2DM), and non-diabetic metabolic syndrome (MetS). In hourly taken blood samples of four healthy probands, the intraindividual 24 h variation of C4, conjugated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
94
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 71 publications
14
94
6
Order By: Relevance
“…We found large variations in fasting BA concentrations both within and between individuals, as depicted in Figure 1. This is in line with studies of non-bariatric subjects, which found large diurnal variations within individuals [41,42] and large variations in production and concentrations between individuals [43,44].…”
Section: Discussionsupporting
confidence: 91%
“…We found large variations in fasting BA concentrations both within and between individuals, as depicted in Figure 1. This is in line with studies of non-bariatric subjects, which found large diurnal variations within individuals [41,42] and large variations in production and concentrations between individuals [43,44].…”
Section: Discussionsupporting
confidence: 91%
“…Neither study reported bile acid measurements in plasma. However, the large diurnal and interindividual variation in plasma bile acid concentrations makes comparative measurements difficult (67). In agreement with this, targeted data mining of bile acids revealed great variation between XN-treated and control Zucker rats, and no significant changes were observed (data not shown).…”
Section: • Mitochondrial Biogenesissupporting
confidence: 57%
“…We find it unlikely that increased BA synthesis alone is sufficient to cause these effects, as we and others have found that BA synthesis also increases during conditions of metabolic impairment, including human obesity and T2D (26,36,37). On the other hand, it is possible that the interruption in enterohepatic circulation of BAs after BPD could play a part.…”
Section: Discussionmentioning
confidence: 65%